Pengembangan KIT IPA Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Materi Gaya Peserta Didik Fase B Sekolah Dasar - Salsabila Fatiha Surur; Aprilia Eki Saputri; Rina Heryani (Pusat Riset dan Inovasi Nasional, 2026)
This development research aims to produce a science learning kit based on Problem Based Learning to enhance problem-solving skills related to force concepts for elementary school students at Phase B. The research employed a research and development approach consisting of needs analysis, product design, development, validation, and limited implementation stages. Needs analysis was conducted through teacher interviews and classroom observations to identify learning conditions and limitations of instructional media in science lessons. Findings from the analysis served as the foundation for designing the science kit and student worksheets aligned with Problem Based Learning syntax and Polya’s problem-solving indicators. The final product consisted of a science kit containing simple experimental tools and a worksheet book guiding student learning activities. Product validation involved a media expert and a subject matter expert to evaluate content accuracy, design quality, and instructional suitability. Media expert evaluation resulted in a feasibility percentage of 93%, while subject matter expert evaluation reached 96.5%, indicating very high feasibility. Limited implementation was carried out among fourth-grade students through pre-test and post-test administration consisting of eight short-answer questions measuring problem-solving ability. Improvement analysis employed the N-gain formula. Results indicated an N-gain score of 0.3 categorized as moderate improvement. Research findings reveal that the Problem Based Learning–based science kit supports meaningful understanding of force concepts and facilitates structured problem-solving processes. The developed product demonstrates potential as an alternative science learning medium that promotes active learning and higher-order thinking skills in elementary education.